GREEN SYNTHESIS AND CHARACTERIZATION OF SILVER NANOPARTICLES FROM ASPERGILLUS FLAVUS STRAIN S4 - Sarakula Prasanthi, Hemalatha V, J. Anitha, Madhava Reddy Ch (Chelonian Research Foundation, 2023)
Many methods have been developed for the synthesis of silver nanoparticles (Ag-NPs), yet disadvantages are there to declined their catalytic activity due to the large size with small surface area. Hence, herein, the fungus mediated synthesis of Ag-NPs has been reported. The synthesized Ag-NPs were further characterized by XRD, SEM, EDS, and UV–Vis spectroscopy to study the particle size, surface, crystalline nature, phase formation of Ag-NPs and the produced particles were found to be 41.9 nm. The antibacterial efficiency of synthesized Ag-NPs was examined on various bacteria including Streptococcus pyrogenes, Escherichia coli, Salmonella typhimurium, Bacillus subtilis. The Ag-NPs could be considered as excellent broad-spectrum antibacterial agent. More prominently, the Ag-NPs produced by Aspergillus flavus exhibited potent antibacterial activity against certain pathogens. Salmonella typhimurium exhibited maximum zone of inhibition 29.16±0.76 at 60 μg/mL with respective to the standard antibiotic 32.53±1.33 at 30 μg/mL concentration. Key Words: Nanotechnology, Silver nanoparticles, Aspergillus flavus, Antibacterial activity